INCUBATION YIELD AS A FUNCTION OF BROILER BREEDER AGE - da Silva, G. F.; Pereira, D. F.; Salgado, D. D.; Ramos, D. D.; de Freitas, L. G. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The factors involved in poultry egg incubation include breeder hen age, which may influence both the external and internal quality of eggs. In this context, this study sought to determine incubation yield among eggs from breeder hens at three ages. A total of 1,728 eggs were obtained from Cobb broiler breeders at three ages (26 weeks, 32 weeks, and 53 weeks) and incubated. At the end of the incubation process, eclosion, hatchability, the percentage of infertile eggs, the time of embryo mortality, and chick weight were all analyzed according to breeder hen age. Analysis of variance was applied to the results, and egg fertility was found to be associated with breeder age, since lower rates of eclosion were found in eggs from younger broiler breeders. Chick weight was also found to be influenced by breeder age, since eggs from older broiler breeders hatched into heavier chicks. However, neither mortality nor hatchability were found to be affected by breeder hen age.